Pomegranate (punicagranatuml.) Peel extract- a study on potential source of pharmacological activities - R.S.ARVIND BHARANI,; S.KARTHICK RAJA NAMASIVAYAM, (International Journal of Pharma and Bio Sciences, 2016)
Pomegranate (Punica granatum L.) has been used for ages in many civilizations for the prevention and treatment of a varied number of health maladies such as Cancer, diabetes, inflammation, dental plaque, dysentery, and to fight malarial parasites and intestinal infections. It is an important source of bioactive compounds such as Ellagitannins and the Punicalagin. In the present study, potential biological activities of aqueous peel extract of pomegranate were carried out. Antibacterial activity was studied against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Salmonella typhii; Antifungal activity against Aspergillus niger and Aspergillus flavus. Antioxidative study was evaluated by DPPH and FRAP assay. Antimicrobial study reveals all the tested bacterial and fungal strains were susceptible to aqueous peel extract as dose dependent manner. Maximum activity was observed in high concentration of extracts. DPPH and FRAP assay showed potential antioxidative activity due to the presence of various flavonoids.